Indirect involvement of α2-adrenoceptors in the mechanical antihypersensitivity effect induced by the spinally administered imidazoline I1 receptor ligand LNP599 in a rat model of experimental neuropathy - Wei, Hong; Vuorenpää, Anne; Laurila, Jonne; Domanskyi, Andrii; Koivisto, Ari; Pertovaara, Antti (Elsevier Inc., 2026)
Here we assess whether neuropathic pain hypersensitivity is attenuated by spinal administration of the imidazoline I1-receptor agonist LNP599 and whether the attenuation involves co-activation of α2-adrenoceptors. Spared nerve injury (SNI) model of neuropathy was used to induce mechanical hypersensitivity in male and female rats with a chronic catheter for intrathecal drug administrations. Mechanical sensitivity and heat nociception were assessed behaviorally in the injured limb. Additionally, GTPγS radioligand binding assay, β-arrestin recruitment and intracellular cAMP levels were used for receptor profiling in vitro. LNP599 (imidazoline I1 receptor agonist) and clonidine (α2-adrenoceptor agonist) produced equal dose-related mechanical antihypersensitivity effects in both sexes. LNP599 attenuated heat nociception preferentially in males, while clonidine reduced heat nociception equally in males and females. Carbophenyline (another imidazoline I1 receptor agonist) had no significant effect on mechanical hypersensitivity or heat nociception in males or females. Mechanical antihypersensitivity and heat antinociception induced by LNP599 in SNI males was prevented by pretreatments with yohimbine or atipamezole (two α2-adrenoceptor antagonists) but not by efaroxan (a mixed imidazoline I1 receptor/α2-adrenoceptor antagonist). In vitro assays indicated that LNP599 does not activate α2A- or other subtypes of α2-adrenoceptors. However, LNP599 was a weak partial agonist for 5-HT2B receptors and bound to sigma-1 and sigma-2 receptors that all are involved in modulation of spinal nociception. The results indicate that the suppression of neuropathic pain hypersensitivity by LNP599 is not due to action on spinal imidazoline I1 receptors, but rather due to indirect activation of spinal α2-adrenoceptors.